(untitled) (Clinics, 2013)
OBJECTIVE: Dengue is a worldwide public health problem with approximately 50 million cases reported annually. The World Health Organization proposed a revised classification system in 2008 to more effectively identify the patients who are at increased risk of complications from dengue. Few studies have validated this new classification system in clinical practice. We conducted a cross-sectional study of patients hospitalized for dengue in Dourados, Mato Grosso do Sul, Brazil, to evaluate the capacity of the two classification systems for detecting severe cases of dengue. MATERIALS AND METHODS: We conducted a cross-sectional study of survey data from the medical records of patients admitted to the University Hospital of the Federal University of Grande Dourados under clinical suspicion of dengue during an epidemic from September 2009 to April 2010. RESULTS: The distribution of patients according to the traditional classification system was as follows: dengue fever, 150/181 (82.9%); dengue hemorrhagic fever, 27/181 (14.9%); and dengue hemorrhagic shock, 4/181 (2.2%). Using the revised classification system, the distribution was as follows: dengue without warning signs, 45/181 (24.3%); dengue with warning signs, 107/181 (59.1%); and severe dengue, 29/181 (15.6%). Of the 150 patients classified as having dengue fever, 105 (70%) were reclassified as having dengue with warning signs or severe dengue. CONCLUSION: These data demonstrate that the revised classification system has greater discriminatory power for detecting patients at risk of progression to severe disease and those needing hospitalization.